Cardiorenal Disease in COVID-19 Patients. (18th March 2022) - Sifaat, Muhtasham; Patel, Pinak; Sheikh, Razan; Ghaffar, Dawood; Vaishnav, Hitesh; Nahar, Ludmila; Rupani, Sonia; Quadri, Syed
Abstract : Coronavirus disease 2019 (COVID-19) is an illness caused by a novel coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Mutations in the genetic coding and the variations in the spike proteins are critical for the virus's mechanism of facilitating fusion with the human host, making the disease more severe. Recent research indicates that comorbidities including diabetes, hypertension, renal disease, heart failure, and atherosclerosis play a significant role in the severity and high mortality rates of (COVID-19), suggesting that perhaps the metabolic syndrome and its components are associated with COVID-19 morbidity. Primarily, angiotensin-converting enzyme 2 (ACE2) receptor is identified as the entrance receptor of SARS-CoV-2. Increased ACE2 expression, endothelial dysfunction plays a vital role in the progression and severity of complications developed due to COVID-19. In this review, we will discuss the association and management of cardiorenal disease and COVID-19.